Growth and Yield of Benggala Grass ( Panicum maximum ) Planted with Legum Alysicarpus vaginalis With Different N and P Fertilizer Dosage - K., Kholqi; Candraasih K., N. N.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study aims to determine and provide information about the growth and yield of Benggala grass (  Panicum maximum  ) which is planted with legumes  Alysicarpus vaginalis  with different doses of Urea (N) and Phosphorus (P) fertilizers. The study was conducted at the Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on Jalan Sesetan. The research lasted for 12 weeks, using a complete randomized design (CRD) split plot pattern consisting of main plots ie 1  Panicum maximum  cropping pattern without  Alysicarpus vaginalis  (A0), 1  Panicum maximum  + 1  Alysicarpus vaginalis  (A1), 1  Panicum maximum + 2  Alysicarpus vaginalis  (A2), 1  Panicum maximum + 3  Alysicarpus vaginalis (A3), and subplots consist of four doses, namely N 0 P 0  kg/ha (D0), N 50 P 25  kg/ha (D1), N 50 P 50  kg/ha (D2), N 75 P 50  kg/ha (D3) there were 16 treatment combinations and were repeated three times so that there were 48 experimental units. The variables observed were growth, yield and characteristics of plant growth. The results showed that the growth and yield of  Panicum maximum  grass on the number of A0 legumes had the highest mean on the variable number of leaves, number of tillers, leaf dry weight, stem dry weight and total forage dry weight. The highest average D3 fertilizer dose on the variable dry weight of leaves, root dry weight and total forage dry weight were statistically significant. The conclusion of this research Panicum maximum  grass that is grown without legumes  Alysicarpus vaginalis  provide the best growth and d osis fertilizer N 75 P 50  kg / ha give the best response in the  Panicum maximum  grass and interaction between mixed cropping amount of legumes with a dose of fertilizer N and P on stem dry weight, root dry weight and total forage dry weight. Keywords : Growth, Yield, Panicum maximum, Alysicarpus vaginalis, Urea, Phosphorus